2019
DOI: 10.1007/s10661-019-7435-y
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of observations of soil organic carbon in Swiss croplands showing stability overall but with some divergent trends

Abstract: The temporal evolution of soil organic carbon (SOC) is of major importance given its status as a key parameter in many soil functions. Furthermore, soils constitute an important reservoir of carbon in our environment. In light of climate change, consistent SOC data over extended periods in combination with information on agricultural management are much required, but still scarce. We report SOC changes in the topsoil (0–20 cm) of Swiss cropland measured at well-defined monitoring sites resampled every 5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…In this study, no evidence of this magnitude of increase was found, and no such difference was seen in neither the original data nor in the log transformed data. When using a similar amount of data from meadows, Gubler et al [76] found that the minimum detectable change in 10 to 100 years (at a power of the 80%, such as in the present study) spanned from approximately 2 to 6%, respectively. Bellamy et al [15] showed that variation in time strongly depended on the initial SOC content, e.g., sites with low SOC had more opportunity to increase their SOC than sites with high SOC.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In this study, no evidence of this magnitude of increase was found, and no such difference was seen in neither the original data nor in the log transformed data. When using a similar amount of data from meadows, Gubler et al [76] found that the minimum detectable change in 10 to 100 years (at a power of the 80%, such as in the present study) spanned from approximately 2 to 6%, respectively. Bellamy et al [15] showed that variation in time strongly depended on the initial SOC content, e.g., sites with low SOC had more opportunity to increase their SOC than sites with high SOC.…”
Section: Discussionsupporting
confidence: 67%
“…The previous analyses based on modelled data over a 15-year span (from 1994 to 2008) predicted a mean relative increase of around the 21% of SOC content in arable lands, but such an increase was affected by a strong variability in the real plot scale land use when survey data was reviewed. By using a monitoring network spanning 30 years, Gubler et al [76] found that SOC dynamic is more determined by a change in land use than other predictors in a colder climate (Switzerland) agro-ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no evidence of this magnitude of increase was found, and no such difference was seen in neither the original data nor in the log transformed data. When using a similar amount of data from meadows, Gubler et al (2019) found that the minimum detectable change in 10 to 100 years (at a power of the 80%, such as in the present study) spanned from approximately 2 to 6%, respectively. Bellamy et al (2005) showed that variation in time strongly depended on the initial SOC content, e.g., sites with low SOC had more opportunity to increase their SOC than sites with high SOC.…”
Section: Discussionsupporting
confidence: 63%
“…The previous analyses based on modelled data over a 15-year span (from 1994 to 2008) predicted a mean relative increase of around the 21% of SOC content in arable lands, but such an increase was affected by a strong variability when survey data was reviewed. By using a monitoring network spanning 30 years, Gubler et al (2019) found that SOC dynamic is more determined by a change in land use than other predictors in a colder climate (Switzerland).…”
Section: Discussionmentioning
confidence: 99%
“…Modelling temporal change can benefit greatly from such repeated measurements, because it filters out spatial variation. In recent years, various countries and organizations have implemented soil monitoring campaigns (e.g., Gubler, Wächter, Schwab, Müller, & Keller, 2019;Orgiazzi, Ballabio, Panagos, Jones, & Fernández-Ugalde, 2018;Smith et al, 2020); making these data available for modelling could greatly improve prediction accuracy. Such monitoring schemes are becoming much easier to practically implement with the use of soil sensing technologies, as reviewed in Smith et al (2020).…”
Section: Recommendations For Improvement Of Predictionsmentioning
confidence: 99%